Diaspora Politics At Home Abroad - Sheffer, Gabriel (Cambridge University Press, 2003)
This book is intended to fill a gap in the study of modern ethno- national diasporas. Against the background of current trends – globalization, regionalization, democratization, the weakening of the nation-state, and massive trans-state migration – it examines the politics of historical, modern, and incipient ethno-national diasporas. It argues that in contrast to the widely accepted view, ethno-national diasporism and diasporas do not constitute a recent phenomenon. Rather, this is a long-standing phenomenon whose roots are in an- tiquity. Some of the existing diasporas were created in antiquity, some during the Middle Ages, and some in modern times. Essential aspects of this phenomenon are the unending cultural-social-economic strug- gles and especially the political struggles of these dispersed ethnic groups, permanently residing in host countries away from their home- lands, to maintain their distinctive identities and connections with their homelands and other dispersed groups from the same nations. While describing and analyzing the diaspora phenomenon, the book sheds light on theoretical questions pertaining to current ethnic politics in general